A new fuzzy decision making approach for personnel selection problem - Konacoglu, Jale; Albayrak, Inci (IOS PRESS, 2018)
In this study, as a strategic decision-making problem, personnel selection is considered for an organization. Personnel selection is very important issue, matching the qualified personnel with the appropriate vacant position considering the assessment of the organization from each interviewee's in the uncertain environment, for the enterprise performance of the organization. In such problems, the presented candidates for the organization should be evaluated based on the criteria that are determined by the organization. For selecting the most suitable personnel, based on the preferred criteria goaled by the organization and satisfied by the candidates, a fuzzy decision-making approach is proposed. The proposed approach allows an opportunity to evaluate personnel under uncertain enviroment determining the criteria as fuzzy numbers. To show the applicability of our approach, an implementation and its Matlab code is presented. Furthermore, this approach can be applied to the many fields for solving the selection problems in imprecise enviroment and the Matlab code can be adapted to the related problems easily.
Keywords: Personnel selection; fuzzy logic; decision making; minimizing and maximizing method; SYSTEM; TOPSIS; Computer Science